Enhance Learning Using Instructional Video In Indices And Logarithms - Muhamad, Mohd Muskhairil Amin (UTeM, 2016)
With the development of technology and also the recommendations of the Ministry of Education in a variety of learning methods in line with 21st century learning, it is expected to helped students in mathematics to understand this topic. The use of diversity in the learning process is hoped to arouse the interest of students to gain knowledge and also establish the student centered approach, no longer fully depended on the teacher. Teachers who used to be a speaker, which uses one way communication, now turned into a facilitator who guides the students through a two-way learning indirectly. In addition, the approach in also allows students to learn at their own pace and also they can learn at any time and without limitation in the classroom only.